2019
DOI: 10.31265/ams-skrifter.v0i26.215
|View full text |Cite
|
Sign up to set email alerts
|

10. Expoloring Age - Transition Analysis as a Tool for Detecting the Elderly

Abstract: The growth of gender archaeology has improved the inclusion of female and juvenile narratives in archaeological discourse, enabling us to better understand interactions between groups defined by both social and physiological differences. There has been a notable absence of elderly in research, however, that is not simply a question of attitudes but of methodological limitations. The emergence of biostatistics has offered novel ways to combat common issues such as age mimicry and avoid the problematic nature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 75 publications
3
7
0
Order By: Relevance
“…When looked at separately, the pubic symphysis generally produces the best estimates followed by the sacroiliac joint, with the cranial sutures finishing a distant third, similar to what another validation study found (Maaranen & Buckberry, 2018).…”
Section: Prior Distributionssupporting
confidence: 75%
“…When looked at separately, the pubic symphysis generally produces the best estimates followed by the sacroiliac joint, with the cranial sutures finishing a distant third, similar to what another validation study found (Maaranen & Buckberry, 2018).…”
Section: Prior Distributionssupporting
confidence: 75%
“…Although TA is a statistical step forward, its age estimates still fall short of what is needed for forensic and archaeological applications, particularly for individuals between 45 and 75 years of age (Milner & Boldsen, 2012c). Despite the method's correction for correlated traits, applications of the method have found lower accuracy (i.e., percentage of individuals falling into estimates ranges that contain their true age) than what would be expected given the use of 95% prediction intervals (Getz, 2017;Jooste et al, 2016;Maaranen & Buckberry, 2018). This finding indicates that the ad hoc correction for trait correlations is not entirely successful.…”
Section: Boldsen Et Al (2002) Methods Performancementioning
confidence: 99%
“…Encouragingly, several studies evaluating TA have found that the commonly held assumption that variation in adult age indicators increases throughout adulthood may be unjustified. Although skeletal variation increases between 45 and 75 years of age, it appears to decrease after this time, as reflected in a narrowing of predicted age intervals (Getz, 2017;Jooste et al, 2016;Maaranen & Buckberry, 2018;Milner & Boldsen, 2012c)4. Additionally, there appears to be acceptably low inter-observer error in most trait scores (Fojas et al, 2018;Jooste et al, 2016), which indicates that results can be reliably compared among observers.…”
Section: Boldsen Et Al (2002) Methods Performancementioning
confidence: 99%
See 1 more Smart Citation
“…As TA2 was developed on American—the Terry—and Portuguese—the Coimbra—collections (Boldsen, Milner, Konigsberg, et al, 2002; Milner & Boldsen, 2012a), a series of validation studies have been performed to test broad population applicability. These have shown the method's suitability for the analysis of the United States (Fojas et al, 2018; Milner & Boldsen, 2012c; Simon & Hubbe, 2021), Colombian (Lopez‐Cerquera & Casallas, 2018), Finnish (Maaranen & Buckberry, 2018), and South African populations (Jooste et al, 2016) (Table 1), while its performance on Asian populations remains unknown.…”
Section: Introductionmentioning
confidence: 99%